KAJIAN KUALITAS AIR WADUK TIRTA SHINTA DI KOTABUMI LAMPUNG - Riyadi, Agung (Jurnal Hidrosfir Indonesia, 2006)
Tirta Shinta reservoir located at Wonomarto, North Kotabumi Lampung. Fiveteen year ago, this reservoir only use for wet rice field irrigation and the depth until 19 meter, but now the depth average just only 6 meter, many activities in the upper land and a lot of sedimentation. This reservoir condition be apprehensive, beside for used by irrigation, cultivation fish (karamba jaring apung) and tourisme, 40% surface water reservoir covered by grass wild and than degradation for fish production. Water quality for the Tirta Shinta reservoir still under standard quality (baku mutu) for fish. Dissolved oxygen (DO) surface water around 5 ppm, but at the bottom decrease until 2 ppm. Bakteri Coli containt is very hight until 1600 MPN/100ml, may be caused by a lot of fish cultivation activities, waste water domestic around the reservoir and no flushing water in the reservoir. Zeng (Zn) more until 0.112 mg/liter exceed quality standard (baku mutu) that is 0.05 mg/l. Ph relative acid around 5.5 6 and Pb under 0.001 mg/l.